Understanding Baseball Consumption Via In-Home Gaming - Joey Gawrysiak; Brendan Dwyer; Rick Burton (Journal of Applied Sports Management, 2014)
Baseball in-home gaming has evolved and expanded from the age of wooden tabletop or cardboard games with spinners and/or dice to the advent of electronic gaming via analytically advanced fantasy baseball leagues and baseball video games. Video games, a new form of social media, are now a multibillion-dollar a year industry in the United States with children, teens, and adults spending significant portions of time playing video simulations of baseball. Baseball video games have consistently evolved to offer highly realistic graphics including visuals and sounds that encourage modern in-home gamers to spend longer times playing. This work aims to shed light on the growing trend of baseball video game popularity, along with technological increases in fantasy baseball gaming, and whether or not these advances are seen as positive or negative for professional baseball in terms of baseball fan avidity and traditional sport consumption. Conclusions drawn appear to show that in-home games are good for baseball and the stadium product. This is an under researched area and one that suggests serious need for additional attention. Practitioners may use this information to effectively shape their sales and marketing practices based on the implications of advanced technology in fantasy baseball and baseball video games.
Keywords: technology; baseball gaming; video games; fantasy leagues